The Ontario Sexual Health Education Update: Perspectives from the Toronto Teen Survey (TTS) Youth - Larkin, June; Flicker, Sarah; Flynn, Susan; Layne, Crystal; Schwartz, Adinne; Travers, Robb; Pole, Jason; Guta, Adrian (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
Sexual health education in schools is a controversial topic. In 2015 an updated version of the sex education program was introduced to schools in the Province of Ontario, Canada. The curriculum received strong criticism from some parents and lobby groups. Similar objections led to the Ontario Liberal government withdrawing the previous sex education program update in 2010. Public debates about the appropriateness of the new curriculum are primarily concerned with the extent to which parents were consulted. Absent from these discussions are the opinions of the curriculum’s target group: students. What do young people have to say about their sexual health education, and how can this information be used to provide more effective programs in schools? In this article we draw on the findings of the Toronto Teen Survey (TTS) (N = 1,216) to discuss youth responses to questions about their experience with sexual health education and the relevance of this information for school-based sexual health education (SBSE). Considering that TTS youth identified schools as their primary source of sexual health education, the survey findings have value for SBSE. In discussing the TTS data in the context of the updated Ontario sexual health curriculum, we provide a youth perspective on the revised sexual health education program that was implemented in the fall of 2015.